Carbon coated SnO2 nanoparticles anchored on CNT as a superior anode material for lithium-ion batteries. Issue 7 (1st February 2016) - Ma, Chunrong; Zhang, Weimin; He, Yu-Shi; Gong, Qiang; Che, Haiying; Ma, Zi-Feng
Abstract : High performance hierarchically structured carbon covering SnO2 nanoparticles on CNTs were synthesized via a facile glucose mediated hydrothermal method and subsequent calcination as an anode for lithium-ion batteries. Abstract : Hierarchically structured carbon coated SnO2 nanoparticles well-anchored on the surface of a CNT (C–SnO2 /CNT) material were synthesized by a facile hydrothermal process and subsequent carbonization. The as-obtained C–SnO2 /CNT hybrid, when applied as an anode material for lithium ion batteries (LIBs), showed a high reversible capacity up to 1572 mA h g −1 at 200 mA g −1 with a superior rate capability (685 mA h g −1 at 4000 mA g −1 ). Even after 100 charge/discharge cycles at 1000 mA g −1, a specific capacity of 1100 mA h g −1 can still be maintained. Such impressive electrochemical performance can be mainly attributed to the hierarchical sandwiched structure and strong synergistic effects of the ultrafine SnO2 nanoparticles and the carbon coating, and thus presents this material a promising anode material for LIBs.